Effect of lead nitrate on the ovaries of the - striped snakehead Channa striatus (Bloch, 1793) - Sharma, Shivani; Vyas, Vipin; Tamot, Sadhna; Jha, Ghanshyam N. (Indian Journal of Fisheries, 2017)
The effect of sublethal concentrations of lead nitrate (0, 8, 18 and 28 mg l-1) on the ovaries of the freshwater murrel Channa striatus (Bloch, 1793) (average length : 20-25 cm; average weight : 50-60 g), randomly distributed (ten fishes per group) into four groups (control, Exp-1, Exp-2 and Exp-3, respectively), were studied in triplicate. Each group of fishes were exposed to lead nitrate for 90 days with the aim to assess the histoarchitectural alterations in the ovaries, at different time intervals. Loosening of connective tissue, deshaped primary oocytes, damaged epithelial layer of oocytes, decreased number of yolk granules in secondary oocytes, upliftment of epithelial layer of secondary oocytes, comparatively decreased number of primary oocytes, necrosis, damaged and irregular shaped oocytes and inflammation were common features in all the three experimental groups exposed to sublethal concentrations of lead nitrate. Severity of the above features increased with increased lead nitrate concentration and duration of exposure.